2016
DOI: 10.1016/j.jngse.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

A study into the effect of cleat demineralisation by hydrochloric acid on the permeability of coal

Abstract: Please cite this article as: Turner, L.G., Steel, K.M., A study into the effect of cleat demineralisation by hydrochloric acid on the permeability Abstract Mineral occlusions in cleats are known to considerably reduce coal permeability. Sequential steady state core flooding experiments with aqueous hydrochloric acid (HCl) solutions were conducted on whole core samples from the Bowen Basin, Australia, to assess the effect of mineral dissolution on core permeability. Cleat minerals were characterised by scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…In contrast, carbonate-rich cap-rock and reservoir core from the Netherlands showed an increase in permeability after reaction with SO 2 -CO 2 and brine due to strong carbonate mineral dissolution (Bolourinejad and Herber, 2015). In a different application, a permeability increase was observed in coal and attributed to calcite dissolution in coal cleats after reaction with HCl; however, permeability subsequently decreased in coals where kaolinite was also present in the cleats via kaolinite fines migration and pore clogging (Turner and Steel, 2016). These various changes in accessible porosity and permeability indicate that several factors including mineral content, organic matter content,…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…In contrast, carbonate-rich cap-rock and reservoir core from the Netherlands showed an increase in permeability after reaction with SO 2 -CO 2 and brine due to strong carbonate mineral dissolution (Bolourinejad and Herber, 2015). In a different application, a permeability increase was observed in coal and attributed to calcite dissolution in coal cleats after reaction with HCl; however, permeability subsequently decreased in coals where kaolinite was also present in the cleats via kaolinite fines migration and pore clogging (Turner and Steel, 2016). These various changes in accessible porosity and permeability indicate that several factors including mineral content, organic matter content,…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Balucan et al presented an acidizing means consisting of a pre-flush (HCl), main flush (HCl-HF), and an overflush (HCl) to improve production in the oil and gas industry. Turner et al launched for the first time an acid-induced mineral alteration of the microstructure of coal using scanning electron microscopy and X-ray [24,25]. It is conceivable that cleats demineralization using hydrochloric acid and hydrofluoric acid can be an effective means to overcome low permeability provided cleat connectivity and permeability are characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Vasyuchkov (1985) reported aqueous HCl (2, 4 and 6%) solutions could enhance the coal permeability dramatically from less than 0.1 mD to over 15.1 mD [12]. Turner et al (2016) There was clear evidence for cleat opening via mineral dissolution as well as mineral mobilization-accumulation. Based on the X-ray microcomputed tomography (μCT) image analyses, they conducted flow simulation and reported that acidizing could enhance permeability not only in the vertical direction but also in the lateral or horizontal direction [13].…”
Section: List Of Tablesmentioning
confidence: 99%
“…For example, few of their results is about the horizontal permeability which is parallel to the face cleats and more realistic than the reported vertical permeability. Additionally, in the core flooding tests conducted by Turner et al (2016), the HCl was injected at the same direction with brine [11], which, to mimic how stimulation would be conducted downhole, should be adopt forward flow to characterise initial permeability, reverse flow with acid to simulate the downhole treatment, and then forward flow again to characterise the final permeability.…”
Section: Acid Stimulationmentioning
confidence: 99%
See 1 more Smart Citation